122 Timing of Dietary Zinc Additions During Gestation for Improved Piglet Survival. (12th April 2022) - Hammers, Kelsey L; Urriola, Pedro E; Schwartz, Mark; Ryu, Moon-Suhn; Gomez, Andres; Johnston, Lee J
Abstract: Gestating sows (n = 267) were used to determine if timing of feeding elevated dietary zinc in a commercial setting would reduce pre-weaning mortality of piglets. Sows from 3 consecutive weekly farrowing groups were assigned randomly within parity to 1 of 3 treatments consisting of: 1) Control: a corn-soybean meal diet containing 125 ppm supplemental Zn supplied by zinc hydroxychloride; 2) Breed-to-Farrow (B-to-F): as Control + 141 ppm supplemental Zn as ZnSO4 (266 ppm total supplemental Zn) fed from 5 d after breeding to farrowing; and 3) Day 110-to-Farrow (D110-to-F): as Control diet fed from breeding to farrowing + 2, 715 ppm supplemental Zn as ZnSO4 (2, 840 ppm total supplemental Zn) starting on d 110 of gestation until farrowing. The statistical model considered fixed effects of treatment, farrowing group, and the random effect of their interaction. Dietary treatments did not influence number of total pigs born or pigs weaned per litter (Table). No differences were observed for any piglet growth criteria evaluated across treatments ( P > 0.05). For B-to-F sows, there was an increase in percent of pigs born alive compared with Control and D110-to-F sows ( P = 0.002). Percentage of stillborn pigs tended to decrease for sows assigned to the B-to-F treatment ( P = 0.052) compared with Control or D110-to-F sows. Feeding elevated zinc throughout gestation increased ( P = 0.015) percentage of low-birth-weight pigs born alive compared with Control sows. Mortality of low-birth-weight piglets did not differ among treatments ( P = 0.592). However, a trend for decreasing post-natal mortality ( P = 0.065) of normal birth weight pigs was observed for pigs born to sows fed elevated zinc. The incidence of low-birth-weight pigs was higher ( P < 0.001) for sows fed the D110-to-F treatment compared with Control sows. Overall, feeding elevated zinc to sows throughout gestation increased the proportion of pigs born alive and marginally increased survival of normal birth weight pigs.